Antibodies to Schmallenberg virus in domestic livestock in Turkey - Azkur, Ahmet Kursat; Albayrak, Harun; Risvanli, Ali; Pestil, Zuleyha; Ozan, Emre; Yilmaz, Oktay; Bulut, Hakan (Springer, 2013)
This, partly retrospective study, was designed to determine the seroprevalence of Schmallenberg virus (SBV), a new Orthobunyavirus first reported in Germany in late 2011, in domestic ruminants from the Middle Black Sea, West, and Southeast regions of Turkey. An indirect enzyme-linked immunosorbent assay was used to screen serum samples collected from slaughterhouse animals between 2006 and 2013. The overall seroprevalence was 335/1,362 (24.5 %) with 325/816 (39.8 %), 5/307 (1.6 %), 3/109 (2.8 %), and 2/130 (1.5 %) recorded in cattle, sheep, goats, and Anatolian water buffalo, respectively. This is the first study to demonstrate the presence of antibodies to SBV in Turkish ruminants; it indicates that cattle are more susceptible to infection than sheep, goats, or buffalo and that exposure of domestic ruminants to SBV in Turkey may have occurred up to 5 years prior to the first recorded outbreak of the disease in 2011.
Keywords: Schmallenberg virus; Cattle; Buffalo; Sheep; Goats